Synthesis of silicone carbide nanowhiskers by microwave irradiation method - Suhaimi Mat Kahar author (Institute of Nano Electronic Engineering, Universiti Malaysia Perlis, 2018)
This main objective of this project is to study the feasibility of synthesis of silicon carbide nanowhiskers from graphite and silica using microwaves heating in an argon atmosphere and to study the effect of processing parameters on the synthesis of SiCnanowhiskers. This main objective was accomplished by the following specific objectives ; to investigate the effect of ratio of expanded graphite (EG) and silica, heating temperature, and heating duration on the formation of SiCNWs in term of morphology compositions, optical properties and purity ; to investigate the effect of types of graphite (expanded grahite and flake graphite) to the formation of SiCNWs in term of morphology compositions, optical properties and purity ; to optimize the synthesis of SiCNWs by microwave heating.